The coffin wood (Scottish Archaeological Internet Reports, 2006)
Only Scots pine and spruce were used in the construction of the coffins, the latter being imported from northern Europe. There was no evidence of dovetailed joints or any level of sophistication in the method of construction and nails were over-used.